Nurture talent to meet demands of new economy, says Rosmah - Borneo Post, (KK) (Borneo Post (KK), 2013)
JAKARTA: The Prime Minister's wife Datin Seri Rosmah Mansor has called on human resource professionals to drive forward the agenda of developing the best talent to meet the demand of the new economy.